The Manifests of explosionalism by Vladimir Boudnik - Capkova, Eva (Bohemica Olomucensia, 2017)
Boudnik's manifests of explosionalism are one of the first samizdats in Czechoslovakia after 1948, and also a rare example where a new - purely Czech - artistic movement has been established. His art theory was partially based on his wartime experience and one of his intentions was the creation of a new kind of art that would be able to change society and prevent future wars. He furthermore wanted to qualify the masses for art, enabling everybody to create art from his past experiences and enrich the art world with these works. Boudnik's art theory based on personal freedom and the phantasy of the viewer could however only have a limited impact and success given the the surrounding conditions in the communist Czechoslovakia.
Keywords: Vladimir Boudnik; explosionalismus; manifesto; art theory; Czechoslovakia; 50s and 60s